Vanadium pentoxide decorated with gold as a reliable platform for surface-enhanced Raman spectroscopy - Novák, David; Socha, Aleš; Kočišová, Eva; Kylián, Ondřej; Procházka, Marek (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2026)
Although semiconductor materials such as vanadium pentoxide (V2O5) are promising non-plasmonic substrates for surface-enhanced Raman scattering (SERS) spectroscopy, their broader use is still hampered by their relatively low SERS enhancement. One strategy to overcome this limitation is to combine these materials with plasmonic noble metallic nanostructures. In this study, we investigate this approach for thin V2O5 nanostructural film decorated with Au (V2O5/Au) fabricated by sputter deposition and combined with thermal annealing. We found that SERS enhancement arises from both electromagnetic and chemical (charge-transfer) enhancement as well as it benefits from the morphology of the Au layer. The presence of the continuous Au film leads to a tremendous enhancement of the SERS signal of methylene blue (MB) as compared with Au-free V2O5 substrates. Under optimised conditions (an Au deposition time of 240 s), the SERS enhancement caused by the Au layer was found to be 1200-fold. Furthermore, spectral mapping across the V2O5/Au substrates shows that the relative standard deviation (RSD) of the SERS signal is less than 35 %, i.e., still sufficiently low for reliable detection. Finally, we successfully applied V2O5/Au substrates for sensitive detection of 5,10,15,20-tetrakis-(N-methyl-4-pyridyl)porphine (TMPyP), and 2,2'-bipyridine (BPy).
Keywords: Vanadium pentoxide; Plasma-based deposition; SERS; Charge-transfer; Electromagnetic mechanism; Gold